(3CQHYhf MOjKGs - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3GdMOjK GdChd, bGd QShd Gddg Udi Gddg Ydjg hSde dh Cf GdYHGO CbdGeG hGdHMQ eOGOG hGdCQV bQWGSG hGdLf MSGH hGdCfS cJGHG eG CMUi aVGFd Ydj Hf CHj WGdHs
(3BNQgG (B:s
(3BNQgG(B: (3GdMOjK GdKdGKhf, bGd QShd Gddg Udi Gddg Ydjg hSde(B: (3jG Ydj Efj QCjJ GSec ebQhfG HGSej aj CQHYI ehGWf (B... (3adeG GfJgjJ Edi SOQI GdefJgi hLOJ ecJhHG Efj CfG Gddgs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdMOjK hGdeUWdMs